Computer classroom learning environments and students' attitudes toward computer courses in tertiary institutions in Thailand - Charik, Kanokporn (Curtin University, 2006)
This thesis is significant in that it is one of the first evaluations of a computer classroom psychosocial learning environment and investigation of associations between learning environment factors and students' attitudes at the tertiary level in Thailand. Both quantitative and qualitative methods were used in this study. Three questionnaires were employed to provide quantitative data: the College and University Classroom Environment Inventory (CUCEI), the Computer Laboratory Environment Inventory (CLEI), and the Attitude towards Computer and Computer Courses (ACCC). The three questionnaires were administered to 905 computer science students in order to investigate their perceptions of their learning environment and associations between this and their attitudinal outcomes. Overall, the results generated from scale internal reliability analysis, mean correlations and ANOVAs suggested that the modified Thai versions of the CUCEI, CLEl, and ACCC are valid and reliable instruments for measuring students' perceptions of computing laboratory learning environments in a Thailand university. The results of an application of the CUCEI and CLEI demonstrated that students had positiveperceptions about their computer classroom learning environment. The qualitative data obtained from student interviews supported the information from questionnaires and provided more detail about the computer classrooms. Measurements of students' attitudes indicated that students enjoyed their classes and thought they were useful. Regarding associations between students' attitudes and perceptions of the computer classroom, most scales of the Thai CUCEI and CLEI, were statistically significantly positively associated with the four scales of the Thai version of the ACCC. Importantly, there were significant negative correlations between scales of the CUCEI, and CLEI with the Anxiety scale.